Factors associated with conflict and styles of conflict management among health professionals - Maja Ćeha; Bojan Joksimović; Mile Despotović; Dejan Bokonjić; Biljana Mijović; Ivana Vukotić; Zlatko Maksimović; Marija Milić (Биомедицинска истраживања, 2023)
Introduction: Conflict is a process during which one person consciously and intentionally makes an effort to prevent the other person’s efforts, some kind of blockade that will lead to interruption in achieving the goals and interests of the other person. Conflicts in the healthcare team are common and can lead to reduced productivity in the work of healthcare professionals, which can have a negative impact on the care and treatment of patients. Methods: This cross-sectional study involved 100 health professionals, nurses and doctors employed in the primary, secondary and tertiary levels of health care. The research was conducted from March to August 2020. A questionnaire on socio-demographic characteristics of respondents, a questionnaire on conflicts of health professionals, and a standardized scale of depression, anxiety and stress with 21 questions (DASS-21) were used to measure the level of subjective depression, anxiety and stress Results: Seventy-four health workers (74%) had experience of conflict in the workplace, doctors (95%) significantly more often than nurses (58%) (p=0.001). Forty percent of health workers stated that communication problems were the most common cause of conflict. Seventy-nine respondents (79%) chose cooperation and compromise as a style in conflict resolution. Doctors chose cooperation more often (84%) than nurses (74%) and the difference was statistically significant (p=0.048). Subjects who had experience of conflict had significantly higher average values of anxiety (8.01±2.12) (p=0.026) and stress (10.32±2.91) (p=0.008) compared to subjects who had no experience of conflict (6.13±1.91; 6.12±2.03). Conclusion: Doctors were significantly more likely to have conflict situations in the workplace. For conflict resolution doctors were more likely to choose a style of cooperation and compromise than nurses who were more likely to choose a style of conflict avoidance.
Keywords: conflict; conflict resolution; health professionals